2014
DOI: 10.1002/2013gc005044
|View full text |Cite
|
Sign up to set email alerts
|

Submarine lava flow direction revealed by neutron diffraction analysis in mineral lattice orientation

Abstract: The ocean crust is formed by the rising of magma from mid-ocean ridges and voluminous (1-30 km 3 ) flows of lava away from ridge axes. However, our understanding of the emplacement kinematics of submarine lava is often limited to plan view geometries of near-axis lava. Drilled cores provide in situ access to the intact internal structure of submarine lavas. We used neutron diffraction to study off-axis lava flows drilled into the uppermost crust of ODP/IODP-Site 1256 (Cocos Plate). We provide quantitative insi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 72 publications
1
6
0
Order By: Relevance
“…Similar to the trends of the principal stress axes in the detected stress states, several local 514 and regional morphologic or tectonic features display NW -SE and/or NE -SW principal Fontana and Tartarotti (2013), and Zucali et al (2014); (4) the paleo-EPR crest orientation, 520 which trends NW -SE (as shown by the magnetic anomalies; see Fig. 1) as well as the MAT, 521 and the NE -SW-trending CNS-2 abandoned at 14.7 Ma (Meschede and Barckhausen, 2000).…”
Section: Nw -Se or Ne -Sw 513supporting
confidence: 61%
See 2 more Smart Citations
“…Similar to the trends of the principal stress axes in the detected stress states, several local 514 and regional morphologic or tectonic features display NW -SE and/or NE -SW principal Fontana and Tartarotti (2013), and Zucali et al (2014); (4) the paleo-EPR crest orientation, 520 which trends NW -SE (as shown by the magnetic anomalies; see Fig. 1) as well as the MAT, 521 and the NE -SW-trending CNS-2 abandoned at 14.7 Ma (Meschede and Barckhausen, 2000).…”
Section: Nw -Se or Ne -Sw 513supporting
confidence: 61%
“…The Lava Pond is likely to flow within a trough oriented NW -SE (similar to the trough 586 detected by Hallenborg et al, 2003) confined at the NE and SW border (hence with a 587 confining pressure along the NE -SW direction) with the possibility of extending only along 588 the NW -SE direction (Fontana and Tartarotti, 2013;Zucali et al, 2014). Thus, the Lava 589…”
Section: Regional Implications and Local Tectonics 533mentioning
confidence: 89%
See 1 more Smart Citation
“…Neutron (and X-ray) diffraction can provide structural information and the quantification of LPO (Baker and Wenk, 1972;Chateigner et al, 2000;Wenk et al, 2001Wenk et al, , 2010Zucali et al, 2010Zucali et al, , 2012Zucali et al, , 2014. By using the Rietveld method (Rietveld, 1969), it is generally possible to obtain the crystallographic properties of the different phases (such as lattice parameters, crystallite size, crystal structure, microstrain, etc.…”
Section: Introductionmentioning
confidence: 99%
“…The samples were cut in cubes of ≈ 1cm edge ( In order to evaluate the Crystallographic Preferred Orientation (CPO) of the samples we used the non-disruptive method of the Quantitative Texture Analysis (QTA) by neutron diffraction, successfully applied on various types of rocks and synthetic materials: in monomineralic quartzites [20], marbles [17], limestones [21], dunite [22] or glaucophanite [23], in poly-phasic rocks, as amphibolite [24,25], quartz-feldspatic mylonitic orthogneisses and gabbros [26,27], subacqueous lavas [28] or sandstones [29].…”
Section: Sample Reference System and Methodsmentioning
confidence: 99%